Lathyrus germplasm collections directory - Mathur, P.N.; Alercia, A.; Jain, C. (2005)
This Directory of Lathyrus germplasm collections is being published using the standard IPGRI format for directories of germplasm collections which contains a standard set of headings for each entry. A template requesting information was circulated to a number of institutes and genebanks and the information collected was formatted and compiled by Dr. P.N. Mathur, Ms. A. Alercia and Dr. C. Jain of the International Plant Genetic Resources Institute. Users are encouraged to provide feedback to the compilers to improve quality and comprehensiveness in the future editions. It is hoped that the Directory will generate more interest in research and development of Lathyrus genetic resources and will promote further the conservation and utilization of this underutilized but important genepool in Lathyrus growing areas of Asia and Africa in particular. The compilers would like to thank those who provided information and support to make the directory possible.